Adsorption of Aqueous Glyphosate N-Phosphonomethylglycine by Manganese Oxides/Mesoporous Silica SBA-15 Composite at High Salinity Condition - Cui, Hao; Li, Qin; Qian, Yan; Zhang, Qiu; Zhai, Jianping (Asian Journal of Chemistry, 2012)
Glyphosate N-phosphonomethylglycine (PMG) is the broad-spectrum herbicide used commonly around the world and the main feature of its production wastewater is high salinity. In this paper, the glyphosate removal by manganese-oxides-coated mesoporous silica SBA-15 (MnO2/ SBA-15) under high background salinity conditions was examined. A chemical precipitation method was employed for MnO2 coating on an ordered mesoporous silica SBA-15 template to obtain a significantly enlarged BET surface area of the adsorbent, which was 963 m2/g. The maximum glyphosate uptake capacity for MnO2/SBA-15 was found to be about 300 mg/g. The Langmuir equilibrium model was found to be suitable for describing the adsorption. Kinetic study showed that the adsorption fitted a pseudo-second-order kinetic model. The effects of different parameters such as pH and coexisted ions were also studied. The results also indicate the potential of adsorbents prepared by coating manganese oxides on porous materials via chemical precipitation in removing glyphosate from high-salinity wastewater.